On Stability of Multi-Valued Nonlinear Feedback Shift Registers - Haiyan Wang; Qiuzhen Lin; Jianyong Chen; Jianqiang Li; Jianghua Zhong; Dongdai Lin; Jia Wang; Lijia Ma (Complexity)
Nonlinear feedback shift registers (NFSRs) are the main building blocks in many convolutional decoders, and a stable NFSR can limit decoding error propagation. Due to lack of efficient algebraic tools, the stability of multi-valued NFSRs has been much less studied. This paper studies the stability of multi-valued NFSRs using a logic network approach. A multi-valued NFSR can be viewed as a logic network. Based on its logic network representation, some sufficient and necessary conditions are provided for globally (locally) stable multi-valued NFSRs, explicit forms are given for the set of basins, and the algorithm for obtaining the set of basins is provided as well. Finally, a new method is presented for constructing stable n+1-stage NFSRs from stable n-stage NFSRs by the properties of D-morphism.